The Effect of Early Mathematical Ability and Mathematical Communication Ability on Mathematical Problem Solving Ability - Christanti Fransina Angel Paulus; Theresia Laurens (Universitas Negeri Makassar, 2023)
This study aims to look at the relationship between early math skills and mathematical communication skills on students' math problem solving abilities. The population in this study amounted to 151 students and a sample of 110 students was taken using the slovin formula. This research uses quantitative methods. The research data was collected through a research instrument in the form of a written test, then processed and analyzed using path analysis techniques. The results of this study indicate that (1) there is a relationship between early mathematical ability and mathematical problem solving ability; (2) there is a relationship between mathematical communication skills and mathematical problem solving abilities;